Shamba showdown ukama ustawi progress report - Shapiro, Jay; Odera, Denis; Kigo, Samm; Girvetz, Evan; Chilambe, Pedro; Waswa, Boaz (2023)
The Shamba Showdown project emerges in response to a critical, yet under-addressed issue in Kenya's agriculture sector: the aging farmer population and the disinterest of the youth in farming. Despite the fact that 85% of Kenya's food supply is domestically grown, primarily by smallholder farmers, there is a looming food crisis driven by the aging demographic of these farmers. The median age of Kenyan farmers is now over 60, and the younger generation, educated in urban areas, shows little inclination to return to rural farming. This trend is not only evident in Kenya but is also a common scenario in many African rural communities. Current developmental efforts in Africa's agriculture focus extensively on enhancing smallholder farmers' productivity through various means, such as precision farming technologies, crop diversity for resilience, and improved market access. However, these initiatives overlook a fundamental challenge: the dwindling interest of the youth in agriculture. Less than 21% of agricultural organizations in Africa consider youth encouragement as a primary goal, according to a study by Heifer International. The Shamba Showdown project aims to tackle this issue innovatively by harnessing the appeal of 3D competitive gaming. The project's objective is two-fold: firstly, to rebrand farming as an attractive and viable career option for the youth, or in other words, to "Make Farming Cool Again." Secondly, it seeks to educate urban youth on managing their family farms remotely, using technology such as smartphones and employing local labor. This approach could be a game-changer in ensuring food security for the upcoming decade and beyond, by engaging a new generation in agriculture. The project represents a significant shift in strategy, focusing on changing perceptions and utilizing modern technology to bridge the rural-urban divide in the agricultural sector.